Removal by dyes from aqueous solution by chitosan in prawn shell : adsorption equilibrium and kinetics - Masita Che Omar (School of Environmental Engineering Universiti Malaysia Perlis, 2011)
Adsorption of brilliant dye from aqueous solution onto cross-linked chitosan composite beads was investigated in a batch systems. Kinetic and isotherm studies were carried out by considering the effects of various parameters, such as initial concentration (50-500mg/L), contact time and pH (2-13). It was found that the dye uptakes were much higher in acidic solutions than those in nueutral and alkaline conditions. Adsorption kinetics data were tested using pseudo-first-order and pseuso-second-order models. Kinetics studies showed that the adsorption followed a pseudo-second-order model. The pseudo-first-order and pseudo-second-order rate constants for different initial concentrations were evaluated and discussed.